An Act for regulating and ordering the Troops that are, or may be raised, for the Defence of this Colony, Article 19 (11 May, 1775) - (:unkn) unknown (General Publisher, 1775)
When a commissioned officer is found drunk on duty, he shall be dismissed from service dishonorably. Non-commissioned officers and soldiers shall be sentenced according to a regimental court-martial.
--
Keywords: PEACE OFFICERS